A Combined Aqueous Two-Phase System and Spot-Test Platform for the Rapid Detection of Escherichia coli O157:H7 in Milk. (February 2018) - Cheung, Sherine F.; Yee, Matthew F.; Le, Nguyen K.; Gomes, Elizabeth A.; Afrasiabi, Zahra; Kamei, Daniel T.
Foodborne illnesses are a public health concern in the United States and worldwide. Recent outbreaks of Escherichia coli O157:H7 have brought to light the need for improved ways to detect foodborne pathogens and minimize serious outbreaks. Unfortunately, current methods for the detection of foodborne pathogens are time intensive and complex. In this study, we designed a spot immunoassay that uses a UCON-potassium phosphate salt aqueous two-phase system (ATPS) for the preconcentration of O157:H7. This platform was tested with samples of O157:H7 spiked in phosphate-buffered saline and milk. The ATPS was found to improve the detection limit of the spot test, yielding detection at 10 6 cfu/mL within 30 min. This is the first known application of ATPSs to spot immunoassays. Moreover, detection was successfully achieved without upstream processing or dilution of the sample prior to testing, thereby further simplifying the detection process. This technology's ease of use, sensitivity, and short time to result highlight its potential to advance the spot test as a viable diagnostic tool for foodborne pathogens.